2015
DOI: 10.1016/j.actbio.2015.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Alkylation of human hair keratin for tunable hydrogel erosion and drug delivery in tissue engineering applications

Abstract: Polymeric biomaterials that provide a matrix for cell attachment and proliferation while achieving delivery of therapeutic agents are an important component of tissue engineering and regenerative medicine strategies. Keratins are a class of proteins that have received attention for numerous tissue engineering applications because, like other natural polymers, they promote favorable cell interactions and have non-toxic degradation products. Keratins can be extracted from various sources including human hair, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
66
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(67 citation statements)
references
References 64 publications
1
66
0
Order By: Relevance
“…We also recently found that rhIGF-1 has minimal interactions with keratin proteins, though interactions are greater for KTN than for KOS. 33 This relatively low interaction allowed us to study the effects of only erosion on this molecule with minimal concern for other effects (e.g., molecular interactions) that might affect release. With recent efforts to better mimic processes of development, increasing numbers of exogenously delivered bioactive molecules will be used in tissue engineering constructs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also recently found that rhIGF-1 has minimal interactions with keratin proteins, though interactions are greater for KTN than for KOS. 33 This relatively low interaction allowed us to study the effects of only erosion on this molecule with minimal concern for other effects (e.g., molecular interactions) that might affect release. With recent efforts to better mimic processes of development, increasing numbers of exogenously delivered bioactive molecules will be used in tissue engineering constructs.…”
Section: Discussionmentioning
confidence: 99%
“…Keratins have been reported as stand-alone materials or with controlled release of therapeutic agents for TERM applications including those in nerve, 15, 21, 22, 23 muscle, 24 skin, 25, 26, 27 and bone. 28, 29, 30 Keratins are known to promote attachment of various cell types including osteoblasts, 31, 32, 33 fibroblasts, 34 hepatocytes, 35 and neural cells, 15 though the mechanisms of attachment are not fully known in all cases. The inflammatory response to keratins is minimal.…”
Section: Introductionmentioning
confidence: 99%
“…The biomaterials should have minimal toxicity and appropriate mechanical properties and provoke minimal inflammatory/immune response that mimics the hierarchical structure of normal tissues . More importantly, the biomaterials should degrade gradually along with the tissue regeneration . Since the optimal degradation rate of scaffold depends on the tissue type to be regenerated, the next generation of scaffolds should demonstrate controlled biodegradation patterns.…”
Section: Introductionmentioning
confidence: 99%
“…While hydrophobic, van der Waals, and electrostatic interactions between the material and growth factor as well as entrapment in the polymer network are inherently present, additional molecules can be introduced into the biomaterial to retard the rate of release. Examples of these immobilization methods include affinity binding such as heparin-binding (Yang et al, 2010 , 2012 ; Jeon et al, 2011 ; Wang et al, 2013 ), ionic interactions such as those provided by chondroitin sulfate (Wang Y. et al, 2010 ; Bae et al, 2012 ), cyclodexterins (Del Rosario et al, 2015 ), protease degradable tethers (Tokatlian et al, 2010 ), succinylation (Tsujigiwa et al, 2006 ), alkylation (Tachibana et al, 2006 ; Han et al, 2015 ), and even covalent conjugation (Shen et al, 2009 ; Zhang et al, 2010 ).…”
Section: Alternative Biomaterials Carriers For Molecules Promote Bone mentioning
confidence: 99%